Electronic commerce adoption in SMEs / Winie Anak Jaret - Jaret, Winie (2007)
Previous studies have indicated that electronic commerce development offers a promising way for business to meet the challenges of the ever changing environment. Buyer can gather information rapidly about the availability of the products or services, evaluate, or negotiate with vendors. However, the study about Small and Medium Enterprises in Malaysia still limited or infancy. Thus, this study is to investigate the electronic commerce adoption by businesses in Small and Medium Enterprises in Malaysia. This study focuses on busbesses at Shah Alam only. This achieved by circulating a set of questionnaire to examine the factors of adoption of electronic commerce application by the SMEs.The study found that the adoption of electronic commerce by SMEs in Shah Alam still at a lower level or can be said as infancy, although the potential benefits were perceived to be important